Admission hypomagnesemia and hypermagnesemia increase the risk of acute kidney injury - Cheungpasitporn, Wisit; Thongprayoon, Charat; Erickson, Stephen B. (Renal failure, 2015)
Background: The association between admission serum magnesium (Mg) levels and risk of in-hospital acute kidney injury (AKI) is limited. The aim of this study was to assess the risk of developing AKI in all hospitalized patients with various admission Mg levels. Methods: This is a single-center retrospective study conducted at a tertiary referral hospital. All hospitalized adult patients who had admission Mg available from January to December 2013 were analyzed in this study. Admission Mg was categorized based on its distribution into six groups (less than 1.5, 1.5-1.7, 1.7-1.9, 1.9-2.1, 2.1-2.3 and greater than 2.3 mg/dL). The primary outcome was in-hospital AKI occurring after hospital admission. Logistic regression analysis was performed to obtain the odds ratio of AKI of various admission Mg levels using Mg with lowest AKI incidence (1.9-2.1 mg/dL) as the reference group. Results: Of 9241 patients enrolled, AKI occurred in 1124 patients (12.2%). The lowest incidence of AKI was when serum Mg was within 1.7-1.9 and 1.9-2.1 mg/dL. A U-shaped curve emerged demonstrating higher incidences of AKI associated with both hypoMg (<1.7) and hyperMg (>2.1). After adjusting for potential confounders, both hypoMg (<1.5 mg/dL) and hyperMg (>2.3 mg/dL) were associated with an increased risk of developing AKI with odds ratios of 1.70 (95% CI 1.31-2.18) and 1.42 (95% CI 1.11-1.81), respectively. Conclusion: Both admission hypoMg and hyperMg were associated with an increased risk for in-hospital AKI.